Effect of Adding Flaxseed in the Diet of Laying Hens on Both Production of Omega-3 Enriched Eggs and on Production Performance - Al-Nasser , Afaf Y.; Al-Saffar, Abdulameer E.; Abdullah, Faten K.; Al-Bahouh, Mariam E.; Ragheb, Gehan; Mashaly, Magdy M. (International Journal of Poultry Science, 2011)
Since eggs are an important part of the human diet and people have strong health awareness, it is beneficiary to produce eggs that are considered healthier products such as omega-3 enriched eggs. Omega-3-fatty acids have been shown to improve the human health in many aspects. Lowering circulating levels of cholesterol and lowering blood pressure are just some of their effects. It has been shown that feeding laying hens with flaxseeds leads to an increase levels of omega-3-fatty acids in the eggs and change the Omega-6 to Omega-3 ratio to an appropriate one. However, studies on the effects of feeding flaxseed to laying hens on both increase levels of omega-3 fatty acids and production performance are limited. Therefore, the purpose of the current study was to study the effects of adding flaxseed in the diet of laying hens on both producing omega-3 enriched eggs and on the production performance. Twenty four wk old Lohmann Selected Line (LSL) laying hens were used in the current study. The hens were divided randomly into four groups, the first received a diet with no flaxseed added and served as a control, the second, third and fourth group received 5.0%, 7.5% and 10% of flaxseed in the diet, respectively. The treatments continued for 32 wks. Egg production and feed consumption were recorded and feed efficiency was calculated. In addition, eggs from the different groups were collected at four, eight and 32 wks following treatment and levels of omega-3 and omega-6 fatty acids were measured and the ratio between the two was calculated. At eight wks following treatment, it was found that using either 7.5 or 10% flaxseed in the diet significantly (p<0.05) increased levels of omega-3 fatty acids in the eggs compared to the control. Levels were 267, 232 and 64 mg/egg for the 10%, 7.5% and control group, respectively. In addition, ratio of omega-6 to omega-3 was 2.33:1, 2.98:1 and 10.05: 1, for the same groups, respectively. Furthermore, adding flaxseed in the diet did not adversely affect egg production, egg weight, or feed efficiency. It can be concluded that using flaxseed in the diet of laying hens can result in producing omega-3 enriched eggs and reducing the omega-6: omega-3 ratio without any adverse effects on production performance.